Effect of Snakehead Fish Nugget and Colored Fruit Juice on Immune Response (CD4, TLC, and Leukocytes) in People Living with HIV (PLWHIV) - Ginta Siahaan; Urbanus Sihotang; Jujuren Sitepu; Iceratnalela Siregar (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2021)
Human Immunodeficiency Virus (HIV) is a virus attacking the body's defense system in people living with HIV (PLHIV), such as Cluster Of Differentiation 4 (CD4), Leukocytes, and Total Lymphocyte Count (TLC). People infected with HIV require adequate macro and micronutrients to improve their quality of life. The content of protein, albumin, zinc, and bioactive substances contained in food ingredients can increase the immune response. Snakehead fish nuggets are rich in Albumin and Zn, while colored fruit juice contains bioactive substances and is high in Vitamin C. This study aimed to determine the impact of snakehead fish nuggets and colored fruit juices on CD4, leukocytes, and TLC in PLHIV in Medan. This research was a Quasi Experiment with a pre and post-test design. The sample represented an entire population of 36 people from all residents of the Rehabilitation Center and was then given the treatment of snakehead fish nuggets and colored fruit juices for 22 days. The data analysis was performed using the T-dependent test after the data were normally distributed. The results showed a treatment impact on CD4, leukocytes, and TLC in PLHIV with a p-value <0.05.Â